Development of in situ PCR for virus detection, strain differentiation and pathogenesis of newcastle disease and infectious bursal disease in chickens - Mahmoud, Hussein Abdallah Elawad (2017)
In molecular methods, there is great probability of virus-specific detection and identification. This is due to genus and family specific genome sequences. In situ PCR appeared into being to comprise PCR power of amplification and in situ hybridization ability to localize target sequence. This new method paves the way to detect minute quantities of nucleic acids in undamaged cells. The objectives of this study were to develop in situ PCR in light microscopy for detection, strains differentiation, and tissue tropism determination of Newcastle disease virus (NDV) and infectious bursal disease virus (IBDV). The method was used to determine pathogenesis of velogenic NDV (vNDV) and very virulent IBDV (vvIBDV) infections.In the first experiment specific pathogen free (SPF) chickens were infected with vNDV by intranasal administration of 0.1 mL of 10⁵ EID50 /0.1 mL of isolate AF2240. Tissue samples were collected and fixed in 10% buffered formalin for histological examination, immunoperoxidase staining (IPS) and in situ PCR. In situ PCR was successfully developed with probe specific for vNDV. In situ PCR (score of 2.17 ± 0.06) was significantly (p<0.05) more sensitive than IPS (score of 1.51 ± 0.40). Histological changes were consistent with the presence of virus. In the second experiment, SPF chickens were inoculated orally with of 0.1 mL of 10⁷·⁵ EID50/mL of vvIBDV (UPM0081 isolate). Tissue samples were collected and fixed in 10% buffered formalin for histological examination, IPS, and in situ PCR. In situ PCR was developed with probe specific for vvIBDV. In situ PCR (score of 2.85 ± 0.29) was significantly (p<0.05) more sensitive than IPS (score of 1.80 ± 0.09). Histological changes were consistent with the presence of virus. In the third experiment, 24 SPF chickens were infected with vNDV (0.1 mL) by intranasal administration of 10⁵ EID50/0.1mL of vNDV AF2240 isolate. Fifteen SPF chickens were kept as control. Chickens were sacrificed at various intervals and tissue samples were collected for histological examination, IPS, and in situ PCR. In situ PCR revealed that at hr 2 post inoculation (pi), virus tended to enter trachea and respiratory tract leading to primary viraemia and invading other organs. At hr 4 pi, virus had entered liver and spleen. However, brain and heart were involved only at hr 6 pi. Secondary viraemia probably started as early as hr 12 pi since vNDVwas positive in all collected tissues. The study showed the descending order of tissues according to positive signal scoring was: trachea, caecal tonsil, liver, bursa of Fabricius, intestine, proventriculus, lung, spleen, thymus, kidney, heart, and brain. IPS findings were almost similar to in situ PCR but less sensitive. Histological changes were consistent with the presence of virus.In the fourth experiment, 24 SPF chickens were infected with vvIBDV (0.1 mL) by oral administration of 107.5 EID50/0.1 mL (UPM0081 isolate). Fifteen SPF chickens were kept as a control group. Chickens were sacrificed at various intervals and tissue samples were collected for histological examination, IPS, and in situ PCR. IBDV was detected in intestine, junction of proventriculus and gizzard and caecal tonsil at hr 2 pi using in situ PCR leading to primary viraemia and invasion of liver, kidney, and bursa of Fabricius. At hrs 4 and 6 pi, virus reached spleen and thymus, respectively. It was detected in muscle on day 1 pi. Hence, secondary viraemia might occur during the period 12 to 24 hrs pi. Virus tissue tropism was summarized briefly in bursa of Fabricius, thymus, caecal tonsil, liver, junction of proventriciulus and gizzard, spleen, kidney, intestine, and muscle. IPS findings indicated sequence of detection of virus, in different tissues, was similar to in situ PCR findings. Histological changes were consistent with findings of in situ PCR and IPS.In fifth experiment, 15 SPF chickens were divided into 3 groups. One group was inoculated with vNDV (0.1 mL) by intranasal administration of 10⁵EID50/0.1 mL of vNDV AF2240 isolate, another group was inoculated with lentogenicNDV strain (lNDV) (V4 isolate) and a third group was kept as control. Tissue samples were collected for detection of virus by in situ PCR with probe specific for vNDV, positive results were obtained only when tissues were infected with vNDV. Similarly, probe specific for lNDV strain showed positive results only for tissues infected with lNDV. It demonstrated that specific probes have ability for differentiation of NDV strains. In the sixth experiment, 15 SPF chickens were divided into 3 groups. One group was inoculated with vvIBDV strain by oral and intraocular administration of 1 mL (10 4.83 EID50/0.1 mL) of UPM0081 isolate, another group was inoculated with caIBDV strain (V877 isolate) and a third group was kept as control. Tissue samples were collected for detection of virus by in situ PCR with probe specific for vvIBDV, positive results were obtained only when tissues were infected with vvIBDV. Similarly, probe specific for caIBDV strain showed positive results only for tissues infected with caIBDV. It demonstrated that specific probes have ability for differentiation of IBDV strains.It was concluded that the study has successfully developed in situ PCR for detection and differentiation of NDV and IBDV strains. In situ PCR was more sensitive than IPS in detection of the virus. Tissue tropisms of the virus and disease pathogenesis were established.